Analysis of the Interaction Interfaces of the N-Terminal Domain from Pseudomonas aeruginosa MutL - Miguel, Virginia (2013)
Mismatch Repair System corrects mutations arising from DNA replication that escape from DNA polymerase proofreadingactivity. This system consists of three main proteins, MutS-L-H, responsible for lesion recognition and repair. MutL is amember of GHKL ATPase family and its ATPase cycle has been proposed to modulate MutL activity during the repairprocess. Pseudomonas aeruginosa MutL (PaMutL) contains an N-terminal (NTD) ATPase domain connected by a linker to a C-terminal (CTD) dimerization domain that possesses metal ion-dependent endonuclease activity. With the aim to identifycharacteristics that allow the PaMutL NTD allosteric control of CTD endonuclease activity, we used an in silico andexperimental approach to determine the interaction surfaces of P. aeruginosa NTD (PaNTD), and compared it with the wellcharacterized Escherichia coli MutL NTD (EcNTD). Molecular dynamics simulations of PaNTD and EcNTD bound to or free ofadenosine nucleotides showed that a significant difference exists between the behavior of the EcNTD and PaNTDdimerization interface, particularly in the ATP lid. Structure based simulations of MutL homologues with endonucleaseactivity were performed that allowed an insight of the dimerization interface behavior in this family of proteins. Ourexperimental results show that, unlike EcNTD, PaNTD is dimeric in presence of ADP. Simulations in mixed solvent allowed usto identify the PaNTD putative DNA binding patch and a putative interaction patch located opposite to the dimerizationface. Structure based simulations of PaNTD dimer in presence of ADP or ATP suggest that nucleotide binding coulddifferentially modulate PaNTD protein-protein interactions. Far western assays performed in presence of ADP or ATP are inagreement with our in silico analysis.